2022
DOI: 10.3390/jof8101062
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome Structure of the Symbiosis between the Desert Truffle Terfezia boudieri and Its Host Plant Helianthemum sessiliflorum

Abstract: The desert truffle Terfezia boudieri is an ascomycete fungus that forms ect-endomycorrhiza in the roots of plants belonging to Cistaceae. The fungus forms hypogeous edible fruit bodies, appreciated as gourmet food. Truffles and host plants are colonized by various microbes, which may contribute to their development. However, the diversity and composition of the bacterial community under field conditions in the Negev desert are still unknown. The overall goal of this research was to identify the rhizosphere mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Nucleosides are considered poor nutritional source for some Bacilli (Schuch et al, 1999), implying that, in the rhizosphere, they may function as signaling chemoattractant molecules rather than a carbon source. Bacilli comprises a substantial portion of the rhizosphere bacterial community (Satish et al, 2022); therefore, it was important to determine whether 2DA serves as nutrient or signaling molecule. Growing B. pumilus and E. coli in M9 medium with glucose or 2DA as the carbon source revealed that the growth rate of both bacteria was inhibited (Figure 5).…”
Section: -Deoxy-adenosine Induces Chemotaxis In Warm-blooded Associat...mentioning
confidence: 99%
“…Nucleosides are considered poor nutritional source for some Bacilli (Schuch et al, 1999), implying that, in the rhizosphere, they may function as signaling chemoattractant molecules rather than a carbon source. Bacilli comprises a substantial portion of the rhizosphere bacterial community (Satish et al, 2022); therefore, it was important to determine whether 2DA serves as nutrient or signaling molecule. Growing B. pumilus and E. coli in M9 medium with glucose or 2DA as the carbon source revealed that the growth rate of both bacteria was inhibited (Figure 5).…”
Section: -Deoxy-adenosine Induces Chemotaxis In Warm-blooded Associat...mentioning
confidence: 99%
“…Another similar species, Trichothecium roseum, has been isolated from rotten pink Chinese truffles and observed on stored desert truffles, Terfeziapinoyi Maire and Terfeziaclaveryi Chatin. This mushroom is a truffle symbiont and, presumably, can be useful for combating soil parasites (Satish et al 2022).…”
Section: Genus Of Bacteriamentioning
confidence: 99%